Hydrodynamic instabilities and entrainment in two-layer stratified flows down a slope - Negretti, Maria Eletta (Dissertationsreihe am Institut für Hydromechanik der Universität Karlsruhe / Universität Karlsruhe (TH), Institut für Hydromechanik, 2007)
Fluid mechanical problems related to two-layer flows are of considerable interest in a variety of geophysical, atmospheric and engineering contexts. A two-layer counter-current flow system over a submerged sill is investigated. The effect of higher Reynolds numbers and of enhanced bottom roughness on the generation and development of hydrodynamic instabilities between the two layers are investigated by means of physical experiments and linear stability analysis.